Studi Pemikiran Pendidikan Ibnu Khaldun Perspektif Sosio-Progresif - Muhammad Zaim (Muallimuna : Jurnal Madrasah Ibtidaiyah, 2016)
IndonesiaDiantara karakteristik yang membedakan pemikiran Ibnu Khaldun dengan pemikran pendidikan tokoh lain yaitu tentang malakah (keterampilan) manusia dalam pengajaran, pendidikan untuk keterampilan pekerjaan, dan tentang peran masyarakat dalam dunia pendidikan. Sehingga karakteristik atau corak pemikiran Ibnu Khaldun inilah yang menjadikan pemikiran pendidikan Ibnu Khaldun di sebut pemikiran pendidikan sosio-progresif.EnglishAmong characteristics that distinguished the Ibn Khaldun's thought with another education thought’s person that was about malakah (skills) of human in teaching, education for job skills, and about the society contribution in education. The characteristics or type of these Ibn Khaldun’s thought that made the Ibn Khaldun’s educational thought called “socio-progressive education”. The purpose of education was achieving the obligations religiosity and fulfilling the necessity to survive. Than Dynamical curriculum of education and emphasized toward the malakah (skills) of thinking and working for the provision of individual and society progress